Mechanisms of long non-coding RNAs in biological phenotypes and ferroptosis of glioma - Yin, Xianyong; Gao, Jiajia; Liu, Zihao; Han, Min; Ji, Xiaoshuai; Wang, Zhihai; Li, Yuming; He, Dong; Zhang, Fenglin; Liu, Qian; Xin, Tao (Frontiers in Oncology, 2022)
Glioma, one of the most common malignant tumors in the nervous system, is characterized by limited treatment, high mortality and poor prognosis. Numerous studies have shown that lncRNAs play an important role in the onset and progression of glioma by acting on various classical signaling pathways of tumors through signaling, trapping, guiding, scaffolding and other functions. LncRNAs contribute to the malignant progression of glioma via proliferation, apoptosis, epithelial-mesenchymal transformation, chemotherapy resistance, ferroptosis and other biological traits. In this paper, relevant lncRNA signaling pathways involved in glioma progression were systematically evaluated, with emphasis placed on the specific molecular mechanism of lncRNAs in the process of ferroptosis, in order to provide a theoretical basis for the application of lncRNAs in the anticancer treatment of glioma.